Abordagens multivariadas na avaliação da resistência do solo à penetração em função da profundidade e manejos - Silva, Geovani José (2012)
Usage and management affect the characteristics of agricultural soil and the penetrometer has been widely used in the evaluation of the effects on the soil profile, detecting possible layers of physical barriers. Exploratory multivariate techniques can report properly the variation of structure and reduce subjectivity in the stratification of soil profile. Therefore, this study was developed in order to: assess the physical-hydrical profile of Red Oxisol and a Red-Yellow Oxisol, with a sandy-clay-loam texture, submitted to degraded pasture (DP), conventional tillage (CT) and direct sowing (DS); to describe through the perspectives of the factorial analysis (FA) and cluster analysis (CA), the profiles of soil resistance to penetration (SRP); verify the adequacy of the SRP data to the exploratory multivariate statistical analysis; select the similar measurement and clustering algorithm and evaluate the consistency and coherence of the stratified soil profiles. For physic-hydrical characterization, it has been estimated in the layers 00-100 and 100-300 mm an estimated gravimetric soil moisture ( ), soil moisture content index ( ), bulk density ( ), relative density ( ), particle density ( ), saturated hydraulic conductivity ( ) and, macro ( ), micro ( ) and total ( ) porosities. For multivariate study of the soil profile, we used data from SRP for every 10 mm of depth, originated from 174 penetrometers trials in each area. The average humidity index varied of 0.442 to 0.845 DP and NT; of 6.38 mm h-1 on the DS surface until 41.5 mm h-1 in the lower layer DP, while Mac of 0.055 cm3 cm-3 DS was half its value in CT and DP. All sets of data of SRP presented themselves suitable for AF. The single linkage method was not appropriate to the stratification profile SRP. The stratifications by AC that resembled the most with the ones of AF were the ones that used the complement of r square and linkage method by arithmetic mean between groups (LA).The AC solutions, using Euclidean distance and the LA method, described the SRP behavior's in depth and in a slightly more consistent form. SRP maximum layers were detected between 20 and 80 mm (DP), 90 and 200 mm (CT) and 40 and 100 mm deep in DS. These results partially contradict the usual praxis that defines this as being a layer of zero to five centimeters in DP or that indistinctly stratifies the soil profiles in layers of 10 cm.